2017
DOI: 10.1007/s00266-017-1043-4
|View full text |Cite
|
Sign up to set email alerts
|

Panniculectomy Outcomes in Patients with End-Stage Renal Disease in Preparation for Renal Transplant

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…21,[28][29][30][31] Graft complication rates were acceptable, based on the literature. 8,20,28,30,32 The presence of a wound complication did not increase the likelihood of developing a graft complication, contrary to the literature. 32,33 However, we suggest that the relationship described in previous studies may actually be mediated through another variable: attendance, and mortality).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…21,[28][29][30][31] Graft complication rates were acceptable, based on the literature. 8,20,28,30,32 The presence of a wound complication did not increase the likelihood of developing a graft complication, contrary to the literature. 32,33 However, we suggest that the relationship described in previous studies may actually be mediated through another variable: attendance, and mortality).…”
Section: Discussioncontrasting
confidence: 58%
“…[8][9][10][20][21][22][23][24][25][26] In a study of patients with a history of solid organ transplant, Zellner et al 27 reported a 14% wound complication rate following plastic surgery procedures. [8][9][10][20][21][22][23][24][25][26] In a study of patients with a history of solid organ transplant, Zellner et al 27 reported a 14% wound complication rate following plastic surgery procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn increases the risk of graft loss. A two-stage approach avoids an extended operation time, a large panniculectomy incision, and a higher blood loss followed by the immediate initiation of the posttransplant immunosuppression [10, 32]. There are studies available considering a simultaneous approach.…”
Section: Discussionmentioning
confidence: 99%
“…Minor complications (cellulitis or superficial wound separation) were recorded in 38% of the patients [10]. Mundra et al [32] reported 10.6% of overall wound complications in their analyzed patient cohort. A possible explanation is, that nationwide inpatient samples only report on in-hospital complications, whereas most wound complications might be observed at the postoperative outpatient visits.…”
Section: Discussionmentioning
confidence: 99%